Neuropeptide hormone bursicon mediates female reproduction in the whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae) - Yu, Hao; Yang, Bin; Wang, Liuhao; Wang, Sijia; Wang, Kui; Song, Qisheng; Zhang, Hongwei (Frontiers in Endocrinology, 2023)
Bursicon, a neuropeptide hormone comprising two subunits-bursicon (burs) and partner of burs (pburs), belongs to the cystine-knot protein family. Bursicon heterodimers and homodimers bind to the lucine-rich G-protein coupled receptor (LGR) encoded by rickets to regulate multiple physiological processes in arthropods. Notably, these processes encompass the regulation of female reproduction, a recent revelation in Tribolium castaneum. In this study we investigated the role of burs/pburs/rickets in mediating female vitellogenesis and reproduction in a hemipteran insect, the whitefly, Bemisia tabaci. Our investigation unveiled a synchronized expression of burs, pburs and rickets, with their transcripts persisting detectable in the days following eclosion.RNAi-mediated knockdown of burs, pburs or rickets significantly suppressed the transcript levels of vitellogenin (Vg) and Vg receptor in the female whiteflies. These effects also impaired ovarian maturation and female fecundity, as evidenced by a reduction in the number of eggs laid per female, a decrease in egg size and a decline in egg hatching rate. Furthermore, knockdown of burs, pburs or rickets led to diminished juvenile hormone (JH) titers and reduced transcript level of Kruppel homolog-1.However, this impact did not extend to genes in the insulin pathway or target of rapamycin pathway, deviating from the results observed in T. castaneum. Taken together, we conclude that burs/pburs/rickets regulates the vitellogenesis and reproduction in the whiteflies by coordinating with the JH signaling pathway.